Precision of VerifyNow P2Y12 Assessment of Clopidogrel Response in Patients Undergoing Cerebral Aneurysm Flow Diversion. Issue 4 (29th August 2018) - Bender, Matthew T; Zarrin, David A; Campos, Jessica K; Jiang, Bowen; Chandra, Arun; Vo, Chau D; Caplan, Justin M; Huang, Judy; Tamargo, Rafael J; Lin, Li-Mei; Colby, Geoffrey P; Coon, Alexander L
Abstract: Background: Dual antiplatelet therapy (DAT), most commonly with aspirin and Clopidogrel, is the standard of care for intracranial stenting, including flow diversion. Clopidogrel response varies by individual. Objective: To investigate the real-world precision of VerifyNow P2Y12 assessment (Accumetrics, San Diego, California) of Clopidogrel response. Methods: Using a prospectively-collected, IRB-approved cerebral aneurysm database 643 patients were identified who were treated with the Pipeline embolization device from 2011 to 2017. Patients with multiple P2Y12 assays drawn within a 24-h window were identified. A single patient could contribute multiple, independent sets. Levels drawn before a 5-d course of DAT and patients who received alternative antiplatelet agents were excluded. Therapeutic range was defined as platelet reaction units (PRU) 60–200. Results: A total of 1586 P2Y12 measurements were recorded; 293 (46%) patients had more than one assay. One hundred forty (22%) patients had multiple P2Y12 measurements within 24 h. These patients accounted for 230 independent 24-h sets. The average P2Y12 fluctuation across all sets was 35 points; the 25th, 50th, and 75th percentiles were 12, 26, and 48 points, respectively. Of the 230 24-h sets of P2Y12 assays, 76% remained within their original therapeutic category: 100 (43%) all therapeutic, 54 (23%) all hypo-responsive, and 21 (9%) all hyper-responsive. Twenty-four percent of patients fluctuated between therapeutic categories when multiple P2Y12 assessments were drawn within a 24-h period: 29 (13%) between hypo-response and therapeutic, 23 (10%) between hyper-response and therapeutic, and 3 (1%) between hypo-response and hyper-response. CONCLUSION: Our experience suggests P2Y12 is an often-imprecise measure, and this should be considered when utilizing P2Y12 levels for clinical decisions.